different answers for implementing summation
조회 수: 1 (최근 30일)
이전 댓글 표시
im trying to implement summation in the following 2 ways:
1.
f1=[10 20 30 40 50]
x1=[1 2 3 4 5]
J=0
for i=1:5
J=J+((f1(i)-a*exp(-(x1(i)-mu)^2/sigma))^2)
end
and 2.
f1=[10 20 30 40 50]
x1=[1 2 3 4 5]
J=0
J=@(f,x) ((f-a*exp(-(x-mu)^2/sigma))^2)
for i=1:5
J(f1(i),x1(i))
end
and im getting different final answers for each.
can anyone tell why?
댓글 수: 0
채택된 답변
Guillaume
2015년 6월 22일
Really, the best way of implementing your summation is option 3 which uses vectorised operations:
f1=[10 20 30 40 50]
x1=[1 2 3 4 5]
J = sum((f1 - a*exp(-(x1 - mu).^2 / sigma)) .^ 2)
Your option 2 looks like it wants to use J to store the result as in option 1 (since it has the line J = 0), but then put a function in J on the following line. In the loop you invoke the function but never assign the result to anything. I'm not sure what you expected to happen with that code. If you want to use an anonymous function, you could write your option 2 as:
func = @(f,x) (f-a*exp(-(x-mu)^2/sigma))^2;
J = 0;
for idx = 1 : numel(f1) %don't hardcode bounds, use numel to get the number of elements
J = J + func(f1(idx), x1(idx));
end
But again, vectorised code is better:
func = @(f,x) (f-a*exp(-(x-mu).^2/sigma)).^2; %note the use of .^ instead of ^
J = sum(func(f1, x1))
추가 답변 (1개)
Andrei Bobrov
2015년 6월 22일
편집: Andrei Bobrov
2015년 6월 22일
J = sum(f1-a*exp(-(x1-mu).^2/sigma)).^2)
for 2 variant:
f1=[10 20 30 40 50]
x1=[1 2 3 4 5]
J1=0
J=@(f,x) ((f-a*exp(-(x-mu)^2/sigma))^2)
for ii=1:5
J1 = J1 + J(f1(ii),x1(ii))
end
참고 항목
카테고리
Help Center 및 File Exchange에서 Logical에 대해 자세히 알아보기
Community Treasure Hunt
Find the treasures in MATLAB Central and discover how the community can help you!
Start Hunting!